FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) BERBASIS KINERJA PADA PEMERINTAH KOTA BITUNG PROVINSI SULAWESI UTARA - Woinalang, Anestasye Agnes; Sondakh, Jullie J.; Ilat, Ventje (Universitas Sam Ratulangi, 2016)
Public demands to create good governance such as accountability for local financial management drives government to increase their effort in achieve successful implementation of performance based budgeting by clearly ensure the related between expenditure allocation and performance with efficiency and effectiveness. This research aims to analyze the affecting of budgeting integration with planning and organizing, comprehensive planning and budgeting system and monitoring and evaluating of APBD simultaneous and partially. This study uses samples for 70 people to test the hypothesis of budgeting integration with planning and organizing, comprehensive planning and budgeting system and monitoring and evaluating of APBD simultaneous and partially used F test and T test with multiple linear analysis method. The result prove that budgeting integration with planning and organizing, comprehensive planning and budgeting system and monitoring and evaluating simultaneous affect significantly to performance based budgeting of APBD. Budgetting integration with planning and organizing and monitoring and evaluating partially affect significantly to performance based budgeting of APBD Keywords : APBD, Reinventing Government, Agency, Kebijakan